(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
This research is all about an application developed in order to make household services more manageable and easy like never before. We have developed an application for Online Service Booking native android application using android studio new version. This paper will also describe the working principle of this app. Admin panel of the application has been developed in PHP language with the help of Code Igniter framework a perfect tool to develop this kind of application. PHPMYADMIN has been used for the development of the database. Also we have used the hosting facility provided by 000webhost to deploy our code onto the server. Google firebase has been used for connecting our both the application as well as the admin panel all together. This application has many type of services. User can choose services according to their need and convenience.